Decomposition of Fraud‐Risk Assessments and Auditors' Sensitivity to Fraud Cues* - WILKS, T. JEFFREY; ZIMBELMAN, MARK F. (Contemporary Accounting Research, 2004)
Practitioners and regulators are concerned that when auditors perceive management's attitude or character as indicative of low fraud risk, they are not sufficiently sensitive to high levels of incentive or opportunity risks in their overall fraud‐risk assessments. In this study, we examine whether a fraud‐triangle decomposition of fraud‐risk assessments (that is, separately assessing attitude, opportunity, and incentive risks prior to assessing overall fraud risk) increases auditors' sensitivity to opportunity and incentive cues when perceptions of management's attitude suggest low fraud risk. In an experiment with 52 practicing audit managers, we find that auditors who decompose fraud‐risk assessments are more sensitive to opportunity and incentive cues when making their overall assessments than auditors who simply make an overall fraud‐risk assessment. However, this increased sensitivity to opportunity and incentive cues appears to happen only when those cues suggest low fraud risk. When opportunity and incentive cues suggest high fraud risk, auditors are equally sensitive to those cues whether they use a decomposition or a holistic approach. We discuss and examine potential explanations for this finding.